St. Kitts and Nevis general election 25 October 2004 (Commonwealth Secretariat LondonGB, 2004)
Presents background information on St. Kitts and Nevis. Outlines the activities of the Expert Team. Looks at democracy and the electoral framework. Deals with certain issues, the poll and the count. Provides conclusions and makes recommendations
Keywords: ELECTIONS